Elementos constituintes de aprendizagem para uma gestão escolar aprendente no Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Campus Cabedelo. - Araújo, Maize Sousa Virgolino de (2013)
This study had as the main objective to analyze the constituent elements of the collective learning environment, in the context of school management of the Federal Institute of Education, Science and Technology of Paraíba, Campus Cabedelo. In order to reach this purpose, the following specific objectives were established: a) Identify the constituent elements of a learning organizational environment, according to the adopted literature for this research; b) Identify the constituent elements of an learning organizational environment in management process of IFPB Campus Cabedelo c) Analyze the identified constituent elements in order to check its positive relevance in school management process. Theoretical reference, structured into four parts: (1) school management, (2) participative management in school, (3) learning organization (4) collective learning, was reference for the selection of the seventeen elements which were considered constituents of learning environment. This research, characterized as basic, with a qualitative approach, deductive and exploratory descriptive, delimited as the investigation field IFPB (Campus Cabedelo), more precisely, the Class Council, Pedagogic Meeting and Board of Directors of this institution, as learning spaces, representatives and significant for the discussions of pedagogic questions. Data collect was made through the application of two instruments: interviews and questionnaires, what resulted on 25 interviewers, among the managers civil servants, teachers and students. Data analysis was based on Bardin s (2011) content analysis. The results showed that among the seventeen elements listed for the theoretical research, as constituent of learning environment, fourteen were considered significant, from whom are highlighted, as a higher positive reference, the democratic management, the participation, the commitment, the responsibility, facing challenges, the ethical behavior and the recognition of human potential. This point out to the development of reflect-do-reflect of democratic management process that is in a process of construction.